Vortex shedding characteristics of multi-column structure with or without horizontal connections. (July 2020) - Liang, Yibo; Tao, Longbin
Abstract: Vortex flow around multiple columns of finite length is ubiquitous in engineering. The present work focuses on the basic fluid physics in terms of the vortex shedding flow patterns and their dependence on structural configurations and flow parameters. Though widely documented in the literature, there is no consensus on certain aspects of the wake characteristics immediately behind the obstacles for a multi-column structure at a relative high Reynolds number range. A comprehensive set of numerical simulations has been conducted to investigate the flow interactions with four square section shaped columns in a diamond configuration, which is complimented by experiments using particle image velocimetry and force measurements in a physical model with Reynolds numbers varying from 3.7 × 10 4 to 6.0 × 10 4 . Horizontal structural members called pontoons were added near the end of the columns to alter the interactions with the surrounding fluid. This work reveals further insights of the fluid physics including the interactions of the vortex shedding processes due to the multi-columns and pontoons. The pontoons are seen blocking the vortices shed from the free end of the column by pushing the recirculation region further away from the free end of each column. In addition to the vortex shedding period being increased, further examination of the wake region indicates that the vortex street tends to be tidier and more structured by adding the pontoons to a basic multi-column structure. The findings will lead to better understanding in vortex shedding fluid physics and improved design in new offshore structure development such as deep-draft semi-submersibles and tension leg platforms. Highlights: Investigate the interactions of vortex shedding processes through PIV and force measurements. Examine the characteristics of vortex shedding processes due to multiple structure members. Reveal insights of the fluid physics including the interactions of the vortex shedding processes. The vortex street is found to be more structured by adding the pontoons to the structure. The vortex shedding period is found to be increased by adding the pontoons to the structure.